Optimalisasi Pajak dan Retribusi Parkir di Kabupaten Bengkalis - Lukman Hakim; Nurhazana Nurhazana (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the optimization of parking tax and parking retribution as strategic components of local revenue enhancement in Bengkalis Regency. The topic is important because parking-based revenue, although possessing substantial potential as a sustainable financial source for regional development, has shown fluctuating performance from 2020–2024 due to gaps in regulation, operational inconsistencies, weak enforcement, and inaccuracies in revenue reporting. This research employs a qualitative descriptive approach with primary data obtained through interviews with officials from Bapenda and Dishub, as well as parking officers and parking users in several designated parking areas. In addition, secondary data such as target–realization reports, standard operating procedures (SOP), and relevant regional regulations were used to support the findings. Data were analyzed using the Miles & Huberman interactive model, including data reduction, data presentation, and conclusion verification. The results indicate that parking tax and retribution management in Bengkalis has not been fully optimal. Several critical issues were identified, such as irregularities in tariff application, discrepancies in ticket distribution, lack of standardized operational guidelines, and limited monitoring capacity, which contribute to the risk of revenue leakage. Although some years show revenue achievement above the established target, the overall performance remains inconsistent and heavily dependent on manual systems. The study concludes that optimization requires strengthening regulatory enforcement, digitalizing payment and monitoring systems, improving human resource capacity, and enhancing coordination between agencies. These findings underscore the importance of transparent, accountable, and technology-based governance to increase efficiency, effectiveness, and overall accountability in local revenue management through parking tax and retribution.